From Tradition to Innovation: The Role of Sea Fennel in Shaping Kimchi’s Microbial, Chemical, and Sensory Profiles - Maryem Kraouia; Maoloni Antonietta; Federica Cardinali; Vesna Milanović; Cristiana Garofalo; Andrea Osimani; Antonio Raffo; Valentina Melini; Nicoletta Nardo; Irene Baiamonte; Lucia Aquilanti; Giorgia Rampanti (Molecules, 2025)
Kimchi, a traditional fermented product made primarily with Chinese cabbage, develops its characteristic flavor through microbial activity and a variety of ingredients. This study explores the incorporation of sea fennel (Crithmum maritimum L.), a halophytic plant rich in bioactive compounds and known for its distinctive aroma, into kimchi. Two fermentation methods were compared: spontaneous fermentation and fermentation using a defined starter culture of four lactic acid bacteria strains. Fermentation was conducted at 4 °C for 26 days, with samples monitored for up to 150 days. Parameters analyzed included pH, titratable acidity, microbial counts, organic acid concentrations, volatile organic compounds (VOCs), and sensory attributes. In the early stages, notable differences in acidity, microbial populations, and VOCs were observed between the two methods, but these differences diminished over time. Sensory analysis indicated similar overall characteristics for both prototypes, although the sea fennel’s aroma and fibrous texture remained perceptible at day 150. VOCs analysis revealed that the fermentation time significantly affected the composition of key aroma compounds, contributing to the final sensory profile. Sea fennel played a key role in shaping the VOC profile and imparting a distinctive aromatic quality. Both fermentation methods led to similar enhancements in flavor and product quality. These findings support the use of sea fennel as an aromatic ingredient in fermented vegetables and highlight the importance of fermentation optimization.